Dinamika Hukum dan Ekonomi Dalam Realitas Perkembangan Ekonomi Islam di Indonesia - Aan Nasrullah (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2021)
The purpose of this research is to examine more deeply the dynamics and relations between law and the economy in Indonesia. Based on the discussion above, a conclusion can be drawn that, First, the dynamics between law and the economy are related to the constitution that applies in a country, law (statutory regulations) exists to guarantee and facilitate the existing economic system, in this case related to economic activities not can be carried out without a conducive situation or condition, then the law in the form of statutory regulations is present to guarantee legal certainty and from this second pattern the law is sometimes more determinant of the economy. Second, based on data and facts from the development of the Islamic economy presented, that the laws and regulations that apply in Indonesia during certain government periods tend to facilitate Islamic-based economic systems and patterns (sharia economy), especially the Islamic economy that is currently developing is also in line with state constitution or aligned with the values of Pancasila and the 1945 Constitution.